2021
DOI: 10.3390/cryst11101172
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial-Based Drug Targeted Therapy for Cardiovascular Diseases: Ischemic Heart Failure and Atherosclerosis

Abstract: Cardiovascular diseases (CVDs) represent the most important epidemic of our century, with more than 37 million patients globally. Furthermore, CVDs are associated with high morbidity and mortality, and also increased hospitalization rates and poor quality of life. Out of the plethora of conditions that can lead to CVDs, atherosclerosis and ischemic heart disease are responsible for more than 2/3 of the cases that end in severe heart failure and finally death. Current therapy strategies for CVDs focus mostly on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…New nano-drug carriers can also be taken up preferentially by immune cells, aiming to control localized inflammatory processes and deliver a therapeutic payload to plaque. Innovative NP composition, formulation, and fictionalization design have improved the field in order to achieve therapeutic effectiveness [72]. This point of view seeks to assess these changes and provide fresh perspectives on how nanotechnology might most effectively help treat cardiovascular disease.…”
Section: Figure 1 Drug Delivery Systems For Diagnosis And/or Therapy ...mentioning
confidence: 99%
“…New nano-drug carriers can also be taken up preferentially by immune cells, aiming to control localized inflammatory processes and deliver a therapeutic payload to plaque. Innovative NP composition, formulation, and fictionalization design have improved the field in order to achieve therapeutic effectiveness [72]. This point of view seeks to assess these changes and provide fresh perspectives on how nanotechnology might most effectively help treat cardiovascular disease.…”
Section: Figure 1 Drug Delivery Systems For Diagnosis And/or Therapy ...mentioning
confidence: 99%
“…Cell regeneration is enhanced by an increase in the number of stem cells in the vicinity of damaged tissues. Stem cell therapy had limited initial applications due to their tendency to migrate to other organs [132]. This limitation is reflected in the fact that only a small proportion (3.5% or less) of infused MSCs can be detected in the ischemic area several weeks after cell infusion [133].…”
Section: Iron Oxide-based Nanoparticlesmentioning
confidence: 99%
“…Atherosclerosis is a chronic arterial disease and represent the leading cause of vascular death globally due to cardiovascular and neurological complications such as ischemic heart and peripheral disease and stroke [ 391 ]. Recent evidence has shown that atherosclerosis is a systemic inflammatory disease in which the accumulation of lipids into arterial wall is mirrored by a pro-inflammatory state driven by chemokines and leukocytes leading to the formation of atherosclerotic plaque [ 392 ]. Atherosclerosis is also known as a disease of aging and the interplay between increasing age and atherosclerosis is still under research.…”
Section: Cardiovascular Aging and Cannabinoid Systemmentioning
confidence: 99%